Evaluationof the Remdesivir Treatment of Non Hospitalized Patients with Covid-19 - Fayaz Ahmed Memon, Kamlesh Kumar Ahuja, Muhammad Tahir, Shahzad Khan Siddique, Anish Kumar, Areesha (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to determine the effectiveness of remdesivir treatment among patients of COVID-19 who were non-hospitalized. Study Design: Randomized/Double blind study Place and Duration: Conducted at Muhammed Medical College & Hospital, Mirpurkhas. Duration was six months from 1st July 2020 to 31st Dec 2020. Methods: There were 170 patients f both genders had confirmed infectious respiratory disease were included in this study. Detailed demographics of enrolled cases included age, sex, body mass and comorbidities were recorded after taking informed written consent. Patients were divided equally into two groups, I and II. 85 patients in group I received placebo for 14 days and group II received remdesivir 200mg first day and 100mg daily for 14 days. Post treatment outcomes among both groups were compared in terms of efficacy, mortality and adverse events. SPSS 23.0 was used to analyze complete data. Results: Among 170 cases, 95 (55.9%) patients were males and 75 (44.1%) were females. In patients of group I mean age was 54.13±7.3 years and in group II mean age was 55.9±8.51 years. In group I diabetes mellitus was found in 45 (52.9%) cases, hypertension in 20 (23.5%) patients, obesity in 15 (17.6%) patients and 5 (5.9%) patents had chronic kidney disease while in group II 50 (58.5%) patients had DM, 22 (25.9%) had HTN, obesity in 10 (11.8%) patients and CKD in 3 (3.5%) cases. At 14th day we found that in group I 42 (49.4%) cases were cured, 14 (16.5%) patients were died while in remdesivir group 73 (85.9%) patients were cured and 5 (5.9%) cases were died. Frequency of adverse events in placebo group was significantly higher and was found in 35 (41.2%) cases as compared to remdesivir group I 27 (31.8%) cases with p value <0.005. Conclusion: We concluded in this study that use of remdesivir was effective among patients of non-hospitalized covid-19 in terms of low mortality rate, minimum adverse events and higher number of efficacy as compared to placebo group.